Synthesis and antimicrobial evaluation of 5-aryl-1, 2, 4-triazole-3-thione derivatives containing a rhodanine moiety. Issue 15 (1st August 2015) - Li, Chao; Liu, Jia-Chun; Li, Ya-Ru; Gou, Cheng; Zhang, Mei-Ling; Liu, Hong-Yan; Li, Xiao-Zhen; Zheng, Chang-Ji; Piao, Hu-Ri
Graphical abstract: Abstract: Three series of 5-aryl-1, 2, 4-triazole-3-thione derivatives containing a rhodanine moiety (5a –k, 6a –i, and7a –i ) have been synthesized, characterized and evaluated for their antibacterial activity. Some of these displayed potent antibacterial activity against several Gram-positive and Gram-negative bacterial strains (including multidrug-resistant clinical isolates) with minimum inhibitory concentration (MIC) values in the range of 4–64 μg/mL and minimum bactericidal concentration (MBC) values in the range of 8–256 μg/mL. Compared with previously reported rhodanine derivatives, these compounds exhibited a broad spectrum of antibacterial activity by means of introducing 4-amino-5-aryl-1, 2, 4-triazole-3-thione moiety. Notably, compound5f exhibited good antibacterial activity against Staphylococcus aureus RN 4220, S. aureus 209, S. aureus 503, Gram-negative bacteria ( Escherichia coli 1924), and Candida albicans 7535 with MBC values of 8 or 16 μg/ml. All of the compounds synthesized in the current Letter were characterized by 1 H NMR, 13 C NMR, infrared and mass spectroscopy.